Mitigating the Digital Divide at Manado State Christian Institute Cyber Christian University in Indonesia’s 3T Regions: A Human Resource Support Framework and Adaptive Pedagogy Model - Carlo Devi Sasuwuk (AMUYA: JOURNAL OF MANAGEMENT, 2026)
This policy paper analyzes the implementation of the Minister of Religious Affairs Decree (KMA) Number 351 of 2023, which designates the State Christian Institute of Manado (IAKN Manado) as the pilot project for a Cyber-based Christian Higher Education Institution. The policy faces serious challenges related to the second-level digital divide, particularly for students living in island regions and 3T areas (Remote, Outermost, and Least-Developed Regions). Instead of ensuring equitable access, the policy risks excluding students due to institutional design weaknesses that are overly focused on technological platforms (platform-centric) while neglecting the development of human-centered capacity building. The core problems stem from a Digital Policy Orientation that Neglects Care, the Absence of Re-skilling Mechanisms for Lecturers in low-bandwidth pedagogy (Koehler & Mishra, 2009), and the Minimal Provision of Effective Remote Psychosocial Support to mitigate isolation (Moore, 1989). These three failures perpetuate a high degree of transactional distance, threaten student retention, and undermine the equity principles of the Cyber University program. The methodology employed is qualitative policy analysis using a descriptive-evaluative approach. This study is a literature-based inquiry (library research) utilizing content analysis of regulatory documents (KMA No. 351/2023; the Distance Education Law), academic literature, and reports concerning the digital divide in Eastern Indonesia. The formulation of policy problems and root causes is based on the USG Analysis (Urgency, Seriousness, Growth), while the conceptual framework integrates Digital Divide Theory (DiMaggio et al., 2004), the TPACK Framework, and Institutional Support Theory. Based on William N. Dunn’s policy scoring analysis, the primary policy recommendation is the issuance of a Rector’s Regulation mandating the establishment of Community Learning Centers (PKBK) and a Local Technical Facilitator (FTL) Recruitment Scheme. This regulation aims to create a decentralized, adaptive, and equitable support system, positioning IAKN Manado as a successful model for Distance Education (PJJ) implementation amid geographical disparities.